2011
DOI: 10.1111/j.1439-0531.2011.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

The SNP Genotypes of Growth Hormone Gene Associated with Reproductive Traits in Tsaiya Ducks

Abstract: Our previous cDNA microarray study showed that the growth hormone (GH) gene may involve in the duck egg formation process. The purpose of this study was to investigate the relationship between GH genotypes of single nucleotide polymorphisms (SNPs) and reproductive traits of Tsaiya ducks. Primer pairs for the coding region in the GH were designed based on the duck genomic sequence. Polymorphisms were detected by polymerase chain reaction (PCR)-single strand polymorphism (SSCP) and were verified by DNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
2
6
0
2
Order By: Relevance
“…Other researchers have observed genotypic effects on production traits [2124]. In our study, two SNP mutations were detected in exon 2 of the GH gene and 10 genotypes were obtained, consistent with previous studies [20].…”
Section: Resultssupporting
confidence: 91%
“…Other researchers have observed genotypic effects on production traits [2124]. In our study, two SNP mutations were detected in exon 2 of the GH gene and 10 genotypes were obtained, consistent with previous studies [20].…”
Section: Resultssupporting
confidence: 91%
“…Early in the 1970s, duck growth hormone (dGH) was purified and identified (Chen et al, 1988;Papkoff and Hayashida, 1972). However, research on the duck growth neuroendocrine regulation mechanism has focused on the detection of single nucleotide polymorphisms (Xu et al, 2007;Chang et al, 2012;Wu et al, 2012), expression patterns (Zhao et al, 2004) and hormone levels (Ge et al, 2000) in single genes, and these studies lacked reproducibility and were not systematic. In China, the results of growth neuroendocrine-regulation research on domestic chickens have been applied as a guide for waterfowl production for many years, although these studies were unscientific and lacked pertinence.…”
Section: Introductionmentioning
confidence: 97%
“…Also, Nie et al [30] found a total of 46 SNPs of which, 5 in exons of GH gene of four divergent chicken breeds. In the research made by Chang et al [25], they found 19 SNPs in a region of 2087 base pairs (bp) in the Tsaiya ducks GH gene of which three coding SNPs were recorded. However, Kansaku et al [19] stated that five single nucleotide polymorphisms (SNPs) were found in the promoter region of the duck GH gene.…”
Section: Discussionmentioning
confidence: 99%
“…One pair of gene-specific primer was used in this experiment according to GH gene sequence (Gene Bank accession no. : AB158760) that had been used before by Chang et al [25].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%